2013
DOI: 10.5194/amt-6-1171-2013
|View full text |Cite
|
Sign up to set email alerts
|

Biases caused by the instrument bandwidth and beam width on simulated brightness temperature measurements from scanning microwave radiometers

Abstract: Abstract. More so than the traditional fixed radiometers, the scanning radiometer requires a careful design to ensure high quality measurements. Here the impact of the radiometer characteristics (e.g., antenna beam width and receiver bandwidth) and atmospheric propagation (e.g. curvature of the Earth and vertical gradient of refractive index) on scanning radiometer measurements are presented. A forward radiative transfer model that includes all these effects to represent the instrument measurements is used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The errors range between −0.3 and +0.1 K. This change from negative to positive bias for the elevation angle was also observed by Meu- (Meunier et al, 2013). Figure 10 shows errors associated with the channel bandwidth effect in Tb differences for different elevation angles.…”
Section: Instrumental Characteristic Effect On Microwave Measurementsmentioning
confidence: 72%
See 3 more Smart Citations
“…The errors range between −0.3 and +0.1 K. This change from negative to positive bias for the elevation angle was also observed by Meu- (Meunier et al, 2013). Figure 10 shows errors associated with the channel bandwidth effect in Tb differences for different elevation angles.…”
Section: Instrumental Characteristic Effect On Microwave Measurementsmentioning
confidence: 72%
“…While the narrower bandwidths show deviations smaller than 0.2 K, the widest ones reach biases that range between −1.7 and 3 K. Meunier et al (2013) found that overestimations could reach values up to 8.5 and −2.5 K of underestimation for some frequencies with the 1 GHz bandwidth. These large deviations are caused when the peaks of the oxygen individual absorption lines are also covered by the bandwidth of one of the channels.…”
Section: Instrumental Characteristic Effect On Microwave Measurementsmentioning
confidence: 96%
See 2 more Smart Citations
“…This assumption becomes important only at low elevation angles, e.g. up to 1-1.5 K in K-band at 5 • elevation angle (Meunier et al, 2013;Navas-Guzmán et al, 2016).…”
Section: Radiative Transfer Modelmentioning
confidence: 99%